Monitoring and health risk assessment of organochlorine pesticides in Karun River and drinking water Ahvaz city, South West of Iran. (3rd April 2022) - Jorfi, Sahand; Poormohammadi, Ali; Maraghi, Elham; Almasi, Halime
Abstract: This study evaluated the concentrations of organochlorine pesticides (OCPs) in inlet and outlet of treatment plant of Ahvaz city. For this purpose, the concentrations of six OCPs, including chlordane, dieldrin, dichlorodiphenyltrichloroethane, heptachlor, lindane, and endrin were measured at three different sites during, 12 months. A gas chromatograph-mass spectrometer (GC-MS) device was applied for the analysis and determination of the target pesticides in the water samples. Non-carcinogenic risk analysis showed that total hazard index was below the acceptable limit and there was no danger to the residents of the area, and the carcinogenic risk was within the acceptable range for both the groups of children and adults. The results implied that the concentrations of the studied pesticides decreased after treatment process. The concentrations of the pesticides were lower than the standard level in all seasons. In the chlorination units (water treatment plants No. 1 and 2) of the treatment plant, the concentrations of OCPs were decreased in winter, while the concentration of these compounds in river water was quite high in summer. The mean total concentration of OCPs in the water samples in August, September, October, November, December, January, February, March, April, May, June, and July were 0.3, 0.073, 0.046, 0.033, 0.01, 0.03, 0.025, 0.026, 0.025, 0.03, 0.21, and 0.04 µg/L, respectively.